Environmental assessment and effectivity of green roofs of selected buildings in Metro Manila - Crisostomo, Nico C.; Marcelo, Alexa Celine Erika C.; Orozco, Christian R. (Quezon City College of Engineering, University of the Philippines Diliman, 2018)
This study seeks to address the current lack of comprehensive assessments and standards for green roofs in the Philippines, and whether installing green roof technology in the Metro Manila setting is beneficial or not. It focuses on the development of an assessment framework for green roofs, by first developing an assessment tool from 34 existing standards and literature. Qualitative and quantitative green roof characteristics and components were identified, ranked, and weighted according to their importance as determined by the number of articles where they were considered to have a positive impact. A pilot study focusing on ambient temperature measurements was conducted on the green roof of a 5-7 storey commercial building, and values were compared primarily with values from a similar non-green roofed building, and secondarily with a baseline value from Singapore. The primary comparison was found to be statistically significant in favor of the green roof values, thus indicating that the observed green roof is much more effective at reducing indoor ambient temperature. The secondary comparison showed that the baseline value from Singapore may not be applicable in the Philippine setting because the mean value obtained is significantly less than that of Singapore. Moreover, the observed green roof achieved scores of 75/100 and 96.74/100 for the qualitative and quantitative assessment tools, respectively. Further studies are recommended so that the baseline values, obtained and unobtained in this study, will be further refined and established, respectively. This shall provide a more accurate assessment of the existing and future green roofs in Metro Manila, and in other settings or conditions where this assessment framework may be applied.
Thesis (Bachelor of Science in Civil Engineering)--University of the Philippines Diliman
Keywords: Green roofs (Gardening) -- Philippines